Stakeholder Theory and Value Creation Models in Brazilian Firms - Vidal, Natalia Giugni; Berman, Shawn; Van Buren, Harry (Review of Business Management, 2015)
This study focuses on how organizations create value for stakeholders, distinguishing between narrow and broad value creation models. Our goal is to understand how top Brazilian firms create value for their stakeholders and describe their value creation activities to stakeholders. We use qualitative content analysis methodology to analyze the sustainability or annual integrated report of the top 25 Brazilian firms by sales revenue. These firms were classified into three main types of stakeholder value creation models: narrow, broad, or transitioning from narrow to broad models. Many of these firms are in a transition state between narrow and broad stakeholder value creation models. We also identified seven areas of concentration by firms in creating value for stakeholders: better stakeholder relationships, better work environment, environmental preservation, increased customer base, local development, reputation, and stakeholder dialogue. This study represents a first step towards understanding the current status of value creation orientation in Brazil.